Przedunijne nadzieje i obawy kryjące się za obrazem średniowiecznych władców zawartym w Rozmowie Polaka z Litwinem (1564) - Gacka, Dorota (Tematy i Konteksty, 2019)
Conversation of a Pole with a Lithuanian, written by Augustine Mieleski Rotundus in July or August 1564, was an answer to the political dialogue titled Quincunx. The dialogue was authored by Stanislaus Orzechowski. In his work he ordered Lithuanians to enter the union with Poland, but in the same work he named them slaves and people deprived of freedom. He also expressed the view that only citizens of kingdoms are free and Lithuanians as inhabitants of a duchy have no liberty. Augustine Rotundus replied to him that not all kingdoms enjoy freedom: citizens are free if they have a good ruler. The present paper consists of two parts. In the first part, I present participants of polemics of 1564 and their dialogues, which are written according to ancient rules. In the second part, I quote the medieval threads from Conversation, in which Rotundus talks about rulers of Poland and emperors of Germany. He proves that Polish kings were not always good rulers. Sometimes dukes were better than kings. Therefore the Grand Duchy of Lithuania is not worse than the Kingdom of Poland. Medieval threads also exhibit preunion hopes and fears of the Lithuanians. We find here the picture of the state and the portrait of the ruler which wanted by them. The state should have a Christian character and law which is well constructed. Furtherly, the ruler should be wise, willing to cooperate with the Church, independent of his wife and free of excessive ambition.